Analysis of the Impact of Energy Efficiency and Renewable Energy on Greenho use Gas Emissions and Economic Growth in EU Member States - Andra-Nicoleta Mecu; Florentina Chitu; Georgiana-Ionela Marin; Gheorghe Hurduzeu (Amfiteatru Economic, 2023)
The European Union has set ambitious goals for both energy efficiency and renewable energy use as part of its strategy to combat climate change. Using a panel data regression model that spans from 2012 to 2021, this study aims to evaluate how energy efficiency and the use of renewable energy sources impact greenhouse gas emissions and economic growth in the member states of the European Union. The findings confirm that energy efficiency and renewable energy production effectively reduce greenhouse gas emissions while also positively influencing economic growth. However, it is important to note that the impact of renewable energy production on economic growth is limited. Therefore, it is crucial to emphasise the role of energy efficiency policies for sustainable development within the European Union. In addition, these findings support the implementation of policies that promote responsible energy consumption and encourage economically and environmentally sustainable development.
Keywords: O44; Q01; Q42; Q50; Q56; 330; climate change; renewable energy; economic growth; energy efficiency.